Modulating Interfacial Charge Transfer Behavior through the Construction of a Hetero-Interface for Efficient Photoelectrochemical Water Splitting - Li Xu; Jingjing Quan; Li Xu; Meihua Li; Chenglong Li; Saqib Mujtaba; Xingming Ning; Pei Chen; Qiang Weng; Zhongwei An; Xinbing Chen (Separations, 2024)
Surface-coupled transition metal oxyhydroxide (TMOOH) on semiconductor (SC)-based photoanodes are effective strategies for improving photoelectrochemical (PEC) performance. However, there is a substantial difference between the current density and theoretical value due to the inevitable interfacial charge recombination of SC/TMOOH. Here, we employ BiVO4/FeNiOOH as a model, constructing the BiVO4/MnOx/CoOx/FeNiOOH integrated system by introducing a novel hetero-interface regulation unit, i.e., MnOx/CoOx. As expected, the optimized integrated system demonstrates a photocurrent density as high as 5.0 mA/cm2 at 1.23 V versus the reversible hydrogen electrode (RHE) under 1 sun AM 1.5G illumination, accompanied by 12-h stability. The detailed electrochemical analysis and intensity modulated photocurrent spectroscopy (IMPS) have confirmed that the high PEC performance mainly originates from the hetero-interface structure, which not only suppresses the interfacial charge recombination by accelerating the photogenerated hole transfer kinetics from BiVO4 to FeNiOOH but promotes the kinetics of surface oxygen evolution reaction (OER). Notably, these findings can also be extended to other structures (CeOx/CoOx), reflecting its universality. This finding has provided a new insight into the highly efficient solar energy conversion in the SC/TMOOH system.